VENTURE CAPITAL AS AN ALTERNATIVE FUNDING FOR MICRO SMALL AND MEDIUM ENTERPRISES (UMKM) IN MEDAN - Chairi, Zulfi; Afrita, Afrita; Yudhistira, Eko (Muhammadiyah University Press, 2019)
ABSTRACTThe Doer of Micro, Small and Medium Enterprises have an important role to make and spur a state economic development. According to the Data of Ministry of Cooperation and UKM (2014), the number of cooperation and UMKM is more than 98% of the total entrepreneur in Indonesia. The number of UMKM is more than 58 million enterprises and contribute to pervade more than 97% of man power or in number is around 107 million people. This is a national asset for the sustainable economic development, but there is a funding problem as a classic problem for UMKM. Venture Capital is the most appropriate fund for UMKM as the source of financial capital. The Investment Model of Venture Capital with the participation of capital or in other funding form into a company as the business partner(Investee) in certain period of time has a good prospect, good potential of value creation, feasible, although not bankable. Modal venture investment is more appropriate to fund the UMKM and Start Up because can give fund to the company which has no standard as a company and operational history. This research is purposed to know the law regulation of UMKM empowerment through venture capital funding in Medan and how the deal between the venture capital funding institution and UMKM. The method is descriptive research which using primary and secondary data.Keywords: MSME, Funding, Venture Capital